Panas-dingin hubungan Malaysia-Indonesia : membina iklim saling percaya - Khadijah Md. Khalid; Shakila Yacob; Persidangan Malaysia-Indonesia (2013 : Kuala Lumpur) (Kuala Lumpur : Universiti Malaya, 2013)
Historical development of relations and conflicts between Indonesia and Malaysia.
Keywords: Indonesia -- Relations -- Malaysia; Malaysia -- Relations -- Indonesia